The effect of feeding animals ad libitum vs. at maintenance level on the in vivo digestibility of mown herbage from two permanent grasslands of different botanical composition. (25th September 2012) - Andueza, D.; Picard, F.; Jestin, M.; Aufrère, J.
Abstract: The aim of this experiment was to study the effect of feeding level (FL) on the digestibility of unconserved forage obtained from two permanent grasslands cut at three different dates during the first cycle of growth. Forage was offered to Texel sheep (wethers), at maintenance level and at ad libitum level. Differences in voluntary intake (VI) between grasslands were also tested. Organic matter digestibility (OMD) measured at ad libitum level and at VI was 13% higher on harvested forage from grassland rich in forbs (GRF) than grassland rich in grasses (GRG) at early herbage growth stages, but these differences were no longer found at later maturity stages. In GRF, there were no differences for OMD, at either FL at the young growth stages, but at the end of the cycle the OMD obtained at ad libitum level (0·56) was higher than that at maintenance level (0·50). However, in GRG, at an early stage of forage maturity, OMD at ad libitum level (0·67) was lower than that at maintenance level (0·70), but this difference was no longer found at the end of the growth cycle. In conclusion, the effect of FL on the digestibility of unconserved forage from permanent grasslands depends on the type of grassland. These differences are mainly explained by the different botanical composition of the grassland types.